Investigating the neuroprotective effect of Copolymer‐1 in acute primary angle closure – Interim report of a randomized placebo‐controlled double‐masked clinical trial. Issue 6 (27th March 2019) - Fan, Kenric Rui‐Pin; Baskaran, Mani; Nongpiur, Monisha E.; Htoon, Hla Mynt; de Leon, John Mark S.; Perera, Shamira A.; Belkin, Michael; Aung, Tin
Abstract: Purpose: To investigate the neuroprotective effect of Copolymer‐1 (Cop‐1) in patients with acute primary angle closure (APAC) in a randomized double‐masked controlled trial. Methods: After initial medical management, APAC patients were randomized to receive either subcutaneous Cop‐1 or placebo within 24 hr and at 1 week. After laser peripheral iridotomy (LPI), subjects underwent serial visual field (VF) tests and retinal nerve fibre layer (RNFL) thickness measurements with spectral‐domain optical coherence tomography. The primary outcome measure was mean number of progressing points (significant slope of ≥ 1 dB per year sensitivity loss) over 16 weeks based on pointwise linear regression analysis, and the secondary outcome measure was the change in RNFL thickness. Results: Thirty‐eight patients (19 in each group) completed the study. Twenty‐five (65.8%) were female, the majority being Chinese (86.8%) with mean age 62.5 years (SD 8.1). Patients in the Cop‐1 group were found to have mean of 0.32 (SD 0.95) progressing points compared to 2.74 (SD 5.31) in the placebo group (p = 0.09), while 3/19 (15.8%) of Cop‐1 treated patients had 1 or more progressing points compared to 7/19 (36.8%) in the placebo group (p = 0.14). There was no difference in change of RNFL thickness between groups (p = 0.57). We found improvement of mean deviation (MD) at week 16 in the Cop‐1 group (p = 0.01) compared to worsening of MD in the placebo group (p = 0.04). Conclusion: After APAC, there was no difference in VF progression (or RNFL thickness change) between Cop‐1 and placebo groups. However, there was improvement of MD in Cop‐1 treated patients.